2021
DOI: 10.1093/gbe/evab065
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Variation of Lactase Persistence Alleles in Sudan and South Sudan

Abstract: Lactase persistence (LP) is a well-studied example of a Mendelian trait under selection in some human groups due to gene-culture co-evolution. We investigated the frequencies of genetic variants linked to LP in Sudanese and South Sudanese populations. These populations have diverse subsistence patterns, and some are dependent on milk to various extents, not only from cows, but also from other livestock such as camels and goats. We sequenced a 316bp region involved in regulating the expression of the LCT gene o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The genetic diversity influencing the LP trait has been studied in Sahelian populations ( Ranciaro et al 2014 ; Hollfelder et al 2021 ). Strong evidence of a founder event in the Rashaayda population was inferred in previous studies of the -13915*G LCT variant ( Priehodová et al 2014 , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The genetic diversity influencing the LP trait has been studied in Sahelian populations ( Ranciaro et al 2014 ; Hollfelder et al 2021 ). Strong evidence of a founder event in the Rashaayda population was inferred in previous studies of the -13915*G LCT variant ( Priehodová et al 2014 , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Strong evidence of a founder event in the Rashaayda population was inferred in previous studies of the -13915*G LCT variant ( Priehodová et al 2014 , 2017 ). This variant is associated with camel herders from the Middle East ( Enattah et al 2008 ; Priehodová et al 2017 ), and its high frequencies in those populations are notably different from populations in Sudan and South Sudan (ranging between 0% and 28%) ( Hollfelder et al 2021 ). However, the highest frequency for this LCT variant (on average 76.5% in 51 individuals) and the highest predicted LP phenotype (95%) have been found in the Rashaayda population residing in the eastern Sahelian region ( Priehodová et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the lactase persistence genotype of the LCT gene continues to express throughout childhood into adulthood, the ability to digest milk into adulthood may lead to nutritional advantages over individuals who are not able to digest milk, potentially affecting adult height. Future studies might examine the prevalence of lactase persistence within the Himba, as recent research has identified the presence of LCT gene alleles within other African pastoralist groups (Hollfelder et al, 2020 ). Therefore, unknown environmental and socioecological factors that extend beyond the realm of our covariates may be outweighing a relationship between height and F ROH , thus masking a relationship between these two variables.…”
Section: Discussionmentioning
confidence: 99%
“…While there were independent domestication events of species such as pearl and finger millet, sorghum, and African rice within sub-Saharan Africa, none of these species were indigenous to the Nile region. There is evidence for the presence of herd animals on the same timescale ( 55 ), however, there are variable patterns of lactase persistence genotypes in the region today, which have been attributed to past selection and gene flow from Southwest Asia ( 56 , 57 ). In China, there is evidence for the in situ domestication of common and foxtail millet between 10,300 and 8700 cal B.P.…”
Section: The Origins and Diffusion Of Agriculture And Animal Domestic...mentioning
confidence: 99%